Ragam Penggunaan Bahasa dalam Rapat dan Arisan Karang Taruna AMOEBA di Yogyakarta: Perspektif Sosiopragmatik - Himawan, Riswanda; Suhardi, Suhardi; Prihadi, Prihadi (Institut Agama Islam Sunan Giri Ponorogo, 2022)
This study aims to analyze the variation of language used in AMOEBA (Bajang Youth and Youth Generation) meetings and social gatherings in Pandak, Bantul, and Yogyakarta. The method used in this research is a descriptive qualitative method. The data was obtained from the recordings made at the wedding ceremony of a community in Bantul Regency. According to Scarlet, the speech act analysis in this study is based on the speech act theory. This research produces written data. The results of the study show that the use of language found in the AMOEBA hamlets of Daleman, Gilangharjo, Pandak, and Bantul are as follows; (1) Switching external codes from Javanese to Indonesian; (2) switching extercodescode from Arabic to Indonesian; (3) internal code-switching from Javanese ngoko to Javanese krama; (4) mix code into; (5) mix the code out; (6) and speech acts which are dominated by the presence of illocutionary speech acts, in the form of expressive speech acts and directive speech acts. Based on the sociopragmatic analysis, the use of the language is strongly influenced by the social conditions of the speaking community, both age, kinship, and the same language, because they live in the same area